Artichoke leaf juice contains antihypertensive effect in patients with mild hypertension. - Roghani-Dehkordi F; Kamkhah A (Journal of Dietary Supplements, 2009)
Lifestyle modifications are effective for the management and prevention of hypertension. We conducted a randomized, placebo-controlled trial to evaluate the efficacy of an oral concentrated leaf juice of artichoke ( Cynara scolymus L.; CS) in patients with mild hypertension (systolic blood pressure [SBP]/diastolic blood pressure [DBP], 140-159/90-99 mmHg). Subjects were randomized into a placebo and two drug groups that received 50 and 100 mg of artichoke juice concentrate. After 12 weeks, SBP significantly reduced as compared with the baseline data in case groups and DBP was significantly lower from the baseline as compared with the placebo group. It is concluded that the use of artichoke juice concentrate may have a blood pressure-lowering effect in mild hypertension.